Metapopulation structures affect persistence of predator-prey interactions - Bonsall, M; French, DR; Hassell, M (2002)
1. We investigate the metapopulation dynamics of an extinction-prone host-parasitoid interaction. 2. Single cell host-parasitoid interactions show diverging oscillations resulting in rapid extinction of both host and parasitoid. By linking cells together into metapopulations and controlling for increased availability of resource, persistence time of the trophic interaction is enhanced. 3. Metapopulation persistence is influenced by spatial structure and local demographics. Using nonlinear mixed models, we show that the persistence time of these host-parasitoid metapopulations is determined by habitat size and local within-patch population dynamics. 4. We use a metapopulation model to show how the role of local demographic population structure and habitat size act concomitantly to affect persistence.